From Prompt to Practice: Swedish Preschool Principals’ Perspectives on AI After Professional Development - Ljungcrantz, Lukas (Proceedings of the International Conference on Networked Learning, 2026)
Artificial intelligence (AI) is increasingly influencing early childhood education (ECE), presenting both opportunities and ethical challenges. Preschool principals, as key pedagogical leaders, play a critical role in guiding this integration. This study investigates how Swedish preschool principals perceive AI following a targeted professional development (PD) workshop. While prior research has examined AI’s potential for teaching and administration, little attention has been given to leadership perspectives and their alignment with core educational values. A full-day PD workshop was conducted with approximately 40 principals, combining lectures, interactive exercises, and scenario-based role play. Participants explored concepts such as AI bias, prompt engineering, and ethical dilemmas using generative AI tools. Survey data were collected from 28 principals immediately after the workshop, providing qualitative insights into their experiences, concerns, and perceived needs. Thematic analysis identified three areas: strategic and pedagogical potential of AI, competence, confidence and critical literacy, and ethical integration and governance. Findings indicate that successful AI adoption in ECE requires structured PD, clear policy frameworks, and a commitment to democratic, equitable and child-centred values. The study also demonstrates how networked learning principles, including collaborative reflection, peer dialogue and distributed leadership, can support ethical and inclusive AI integration.